Ovarian inguinal hernia - Amreen, Saika (J Ultrason, 2020)
Indirect inguinal hernia is a common congenital abnormality in children. In female infants, herniation of the ovaries, fallopian tubes and uterus has been reported. Herniation of the ovaries is a rare congenital condition that may be complicated by strangulation, torsion, and infertility. A 6-week-old female infant presented with visible swelling in the right inguinal region. This case highlights the utility of ultrasonography as a cheap and easily available imaging technique that can be used for the characterization of the hernial contents, and guide the management, further accentuated by the use of color Doppler imaging, of this subtle but crucial entity.